Surviving in Power: Japanese Prime Ministers and the 1994 Electoral Reform. Issue 4 (27th October 2015) - Yamamoto, Chika; Jamison, J. Weston
Abstract : How does the 1994 electoral reform affect the rapid turnover of Japanese prime ministers in recent years? This article explores possible ways that the electoral reform affects the duration of Japanese leadership tenure and empirically assesses three hypotheses regarding this effect. Statistical analysis from the late 1960s to the end of the 2000s suggests that the effect of the reform depends on a prime minister's popularity. The institutional structure enforces the negative effects of public disapproval on leadership duration but rarely affects popular leaders. In other words, under the new reform, only prime ministers with rapidly declining public support face a tremendous risk of being short‐lived leaders. This also means that public disapproval matters more for durability of administrations under the new electoral system than under the old system.